Development of the National Library of the Czech Republic 2011–2016: Past, Present and Future. Issue 3 (December 2014) - Böhm, Tomáš
The National Library of the Czech Republic, which was founded in 1773 by the Austrian Empress Maria Theresa, is one of the oldest National Libraries in Europe. It has been through various organizational changes incorporating other libraries and institutions. In addition to providing traditional library service, the library is active in such fields as digitization, paper documents restoration and preservation, refurbishment of its main seat in the baroque Klementinum building and international cooperation. The most important digitization project is the creation of the National Digital Library, which will also serve as the LTP (Long Term Preservation) repository for other digitization projects carried out by either the National Library or by other libraries and institutions in the Czech Republic. Other projects in this field are: the world's biggest digital manuscript library (Manuscriptorium), creation of the Web Archive, digitization of rare books in partnership with Google, formation of the repository for digitized Czech cultural heritage and, together with other main Czech libraries, work on the creation of the Czech Libraries Portal. The Library is further active in paper documents restoration and preservation where it is trying to tackle the problem of de-acidification as well as the formation of the physical Czech Depository Library and the Interdisciplinary Methodological Centre for Book Restoration and Conservation. The Library continues to serve its users during the refurbishment of the Klementinum. It aims to create 'a modern library in baroque walls' by the end of 2018. Furthermore, a new physical depository has been bulk on the outskirts of Prague.